2022
DOI: 10.1016/j.omtn.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of N6-methylandenosine regulators and m6A-related RNAs as prognosis factors in colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignancies and has been a leading cause of cancer-related death worldwide in recent years. N6-methyladenosine (m6A) methylation is the most abundant epigenetic modification of various types of RNAs, and it plays a vital role in promoting cancer development. Here, we obtained SNV and transcriptome data of CRC from The Cancer Genome Atlas (TCGA). We demonstrated that most m6A methylation regulators were aberrantly expressed in individuals with CRC. The abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…As a computer science and high-throughput sequencing technology developed, bioinformatic analysis can provide researchers with more opportunities to explore the genetic risk, regulatory mechanism, and protein function of cancer. As a highly representative bioinformatics database, the TCGA database is generated by large-scale gene sequencing, which can quantitatively study and analyze the changes in gene expression during tumor occurrence and development [ 24 , 25 ]. Therefore, in this study, we performed a series of in-depth explorations of membrane lipid biosynthesis in BRCA based on the TCGA database using multiple bioinformatic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…As a computer science and high-throughput sequencing technology developed, bioinformatic analysis can provide researchers with more opportunities to explore the genetic risk, regulatory mechanism, and protein function of cancer. As a highly representative bioinformatics database, the TCGA database is generated by large-scale gene sequencing, which can quantitatively study and analyze the changes in gene expression during tumor occurrence and development [ 24 , 25 ]. Therefore, in this study, we performed a series of in-depth explorations of membrane lipid biosynthesis in BRCA based on the TCGA database using multiple bioinformatic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) modification is among the most ubiquitous epigenetic modifications of mRNAs and noncoding RNAs (e.g., miRNAs and lncRNAs) [45]. Overwhelming evidence indicates that the dysregulation of m6A modification is significantly correlated with CRC tumorigenesis and progression [46,47]. lncRNAs and miRNAs are not only important targets of m6A modification regulators; they also regulate m6A modification [48,49].…”
mentioning
confidence: 99%
“…As such, there is an urgent Numerous recent studies have demonstrated that hypomethylation results in gene overexpression, whereas hypermethylation causes low gene expression, which plays an important role in the occurrence and progression of various tumors (25,26). It is possible that abnormally methylated genes can cause gene expression disorders, transcriptional disorders, and abnormal differentiation of cells (27). Jiao et al previously provided evidence that SEPT9 methylation may be a biomarker for the diagnosis of cervical cancer, which functions by promoting tumorigenesis and radiation resistance of cervical cancer by targeting the HMGB1-Rb axis, and induces macrophage polarization by mediating Mir-375.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous recent studies have demonstrated that hypomethylation results in gene overexpression, whereas hypermethylation causes low gene expression, which plays an important role in the occurrence and progression of various tumors ( 25 , 26 ). It is possible that abnormally methylated genes can cause gene expression disorders, transcriptional disorders, and abnormal differentiation of cells ( 27 ). Jiao et al.…”
Section: Discussionmentioning
confidence: 99%